Comparative Effectiveness of Islamic Spiritual Care and Physical Relaxation in Controlling Blood Pressure among Hypertensive Patients - Putry, Mayang Novyanti; Wisuda, Aris Citra; Dwi Saputra, Ardi; Suraya, Citra; Hamdan, Ichsan Nur; Martilopa, Iis; Budiyono, Arif; Erpina, Eli; Sari, Indah Tirta (International Journal Scientific and Professional, 2025)
Hypertension remains a major public health problem worldwide and is a leading risk factor for cardiovascular morbidity and mortality. Beyond pharmacological treatment, complementary approaches such as spiritual care and relaxation techniques have been increasingly recognized as effective strategies for managing blood pressure. This study aimed to compare the effectiveness of Islamic spiritual care and physical relaxation in controlling blood pressure among hypertensive patients.A quasi-experimental study was conducted at RSUD Sungai Lilin, South Sumatra, Indonesia, from February to April 2025. A total of 120 hypertensive patients were recruited using total sampling and divided into two intervention groups: Islamic spiritual care (n = 60) and physical relaxation (n = 60). The Islamic spiritual care intervention consisted of guided dhikr and prayer-based relaxation, while the physical relaxation group received progressive muscle relaxation training. Blood pressure was measured before and after the 4-week intervention. Data were analyzed using paired and independent t-tests to compare within-group and between-group differences. Both interventions significantly reduced systolic and diastolic blood pressure compared to baseline (p < 0.05). However, patients receiving Islamic spiritual care demonstrated a greater mean reduction in systolic blood pressure (−12.8 ± 6.4 mmHg) and diastolic blood pressure (−8.6 ± 4.7 mmHg) compared with those in the physical relaxation group (−8.3 ± 5.9 mmHg and −5.2 ± 4.1 mmHg, respectively; p < 0.05). Islamic spiritual care and physical relaxation are both effective in reducing blood pressure among hypertensive patients. Nevertheless, Islamic spiritual care appears to provide greater benefits, suggesting its potential as a culturally appropriate complementary intervention in hypertension management.